Analisis Risiko K3 dengan Metode HIRADC pada Industri Pengolahan Makanan Laut di Jawa Timur - Radityazty Dahayu Nurhayati; Yayok Suryo Purnomo (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
As a company engaged in the food sector, the seafood processing industry certainly prioritizes the freshness of ingredients to maintain the quality of its products. Various existing processes can pose a potential hazard caused by the work environment. It is necessary to identify and analyze the work and the hazards that may arise. HIRADC, which stands for Hazard Identification, Risk Assessment, and Determining Control, is a systematic, thorough, and structured method for identifying various problems that affect processes and risks related to equipment that can harm people. existing equipment or systems. This research is qualitative in nature with a risk analysis approach to the safety of workers working in engineering departments including workshops, maintenance, transformer rooms, generator rooms, boilers, compressors, ice flakes, and WWTP (Wastewater Treatment Plant) in the seafood processing industry in Lamongan, East Java. The results obtained were 37 types of work implementation with 40 hazard risks. Each hazard risk is classified into a low category of 1 hazard risk, a medium category of 31 hazard risks, and a high category of 8 hazard risks. The hazard risk assessment after control was carried out resulted in a low category of 34 risks and a medium category of 6 risks.